Iodocyclization of o-Alkynylbenzamides revisited: formation of Isobenzofuran-1(3H)-imines and 1H-Isochromen-1-imines instead of lactams - Schlemmer, Claudine; Straub, Bernd Franz (The journal of organic chemistry, 2012)
The iodocyclization of o-alkynylbenzamides with various electrophiles has been reported to yield five- or six-membered lactams by nucleophilic attack of the amide nitrogen onto the triple bond. While the formation of an isobenzofuran-1(3H)-imine with two bulky substituents under Larock conditions was initially attributed to steric hindrance, we found out that cyclization via the amide oxygen is the rule rather than the exception. Thus, the structures of the products reported in the literature need to be revised.